EDUCATIONAL GAME RECOGNIZING NATIONAL DAY IN INDONESIA USING MECHANICS DYNAMICS AESTHETICS METHOD - Liany, Dony; Komamrudin, Agus; Yuniarti, Rezki (Journal of Informatics and Communication Technology (JICT), 2023)
The history of national day can remind us of the struggle of the heroes who defended independence with great difficulty. Currently, the history of national days in Indonesia is slowly starting to be forgotten, therefore an educational game about the history of national days has been created which can remind us of the struggles of the heroes who have worked hard to defend Indonesia's independence. There have been many discussions regarding educational games on the history of national days, but they are still limited to platforms without any action in these educational games. This research creates an educational game, where this educational game has a type of learning media in the educational game content of the history of national days. Not a few people know about the national days in Indonesia. The material that will be presented in this educational game is material contained in the history of national days. With the aim of inviting and reminding you about important moments in Indonesia's national days. The benefits that will be received are in the form of learning about the history of national days related to caring behavior about what the heroes have fought for. This educational game was built using the Mechanics Dynamics Aesthetics framework method.